Development of artificial blood loss and duration of excision score to evaluate surgical difficulty of total laparoscopic anterior resection in rectal cancer - Lv, Jingfang; Guan, Xu; Wei, Ran; Yin, Yefeng; Liu, Enrui; Zhao, Zhixun; Chen, Haipeng; Liu, Zheng; Jiang, Zheng; Wang, Xishan (Frontiers in Oncology, 2023)
Purpose: Totally laparoscopic anterior resection (tLAR) has been gradually applied in the treatment of rectal cancer (RC). This study aimed to develop a score system to predict the surgical difficulty of tLAR. Methods: RC patients treated with tLAR were collected. The Blood Loss And Duration of Excision (BLADE) score system was built to assess the surgical difficulty by using restricted cubic spline regression. Multivariate logistic regression was used to evaluate the effect of BLADE score on postoperative complications. The random forest (RF) algorithm was used to establish preoperative predictive model for BLADE score. Results: 1994 RC patients were randomly selected for the training and the test set and 325 RC patients were identified as external validation set. The BLADE score which was built based on the thresholds of blood loss (60 ml) and duration of surgical excision (165 minutes) was the most important risk factor for postoperative complication. The areas under curve of predictive RF model were 0.782 in training set, 0.640 in test set and 0.665 in external validation set. Conclusion: This preoperative predictive model for BLADE score presented clinical feasibility and reliability in identifying the candidates to receive tLAR and making surgical plan for RC patients.